The severity of COVID-19 infection in patients with anorexia nervosa: an observational study. (November 2021) - Taylor, Michael J; Okereke, Uju; Wilson, Robert; Winston, Anthony
Abstract: Background: Patients with anorexia nervosa frequently show neutropenia, lymphopenia, and a reduced CD8 count; pro-inflammatory cytokines tend to be upregulated. The immunological response to bacterial infection is often impaired, but viral illness appears to be rare. At the beginning of the COVID-19 pandemic, clinicians expected that patients with anorexia nervosa would be at increased risk of severe infection. The present study investigated COVID-19 severity in patients with anorexia nervosa with positive SARS-CoV-2 polymerase chain reaction (PCR) tests. Methods: A database was created at NHS England and Improvement, and eating disorders clinicians across the UK reported demographics, clinical characteristics, biomarkers, and outcomes of patients with anorexia nervosa and COVID-19 between May 20, 2020, and May 11, 2021. Eating disorder diagnoses were made by referring clinicians following standard clinical practice. This report follows STROBE guidelines. Findings: Data were collected from 47 patients (44 female) aged 13–57 years (mean 26·8 years [SD 12·3]), including 34 adults (body-mass index [BMI] 12·0–21·3 kg/m 2, mean 15·6 kg/m 2 [SD 2·3]) and 13 children (percentage median BMI 68·5–129%, mean 94·0% [SD 13·4]). 37 patients (79%) had at least one of the typical COVID-19 symptoms of fever, cough, or disturbed smell or taste. One patient was asymptomatic; 44 had mild disease; two developed pneumonia, which for one patient was severe. One patient (2%) required treatment for COVID-19 in a general hospital. In comparison, in the general population of England, between 2·4% and 2·7% of adults aged 18–54 years with a positive SARS-CoV-2 PCR between October, 2020, and February, 2021, were admitted to hospital. Interpretation: To our knowledge, this is the first published study investigating effects of COVID-19 on patients with anorexia nervosa. Contrary to expectations, these findings suggest that anorexia nervosa does not increase the risk of severe COVID-19 infection. They also provide an insight into the effect of malnutrition on COVID-19, and viral infection in general, and offer some reassurance for patients with anorexia nervosa and clinicians about the risk from infection. Additionally, they may inform vaccination and infection control recommendations for patients with anorexia nervosa in future pandemics. The sample size was small and dependent on data submitted by clinicians; the results should therefore be treated with caution. Funding: None.